A Comparative Study of Medical Practices in Ancient China and Greece: Techniques, Ethics, and Influence - Li, Li; Abbas, Syed Tahir; Hui-yun, Guo (PT FORMOSA CENDEKIA GLOBAL, 2024)
This paper explores the scientific and technological contributions of ancient China and ancient Greece, highlighting key innovations and their lasting impacts. Ancient China was characterized by a practical and empirical approach to scientific inquiry, resulting in significant advancements in agriculture, astronomy, medicine, engineering, and information dissemination. Greek contributions to medicine, guided by the Hippocratic Oath, laid the groundwork for ethical medical practice. Greek engineering and architectural innovations, exemplified by structures like the Parthenon, demonstrated their mastery of design and aesthetics. Greek advancements in astronomy and the philosophical ideas of Socrates, Plato, and Aristotle profoundly shaped Western scientific methodology and intellectual traditions. By comparing these two civilizations, the paper underscores the importance of both practical application and theoretical inquiry in the development of science and technology. The influence of cultural and philosophical contexts on scientific inquiry is also examined, highlighting the interplay between science, technology, and society. The legacies of ancient China and ancient Greece have profound implications for our understanding of the development of science and technology, emphasizing the cumulative nature of scientific progress and the enduring value of ancient knowledge. This study provides valuable insights into the rich heritage of these two great civilizations, offering inspiration for future advancements and the continued integration of ancient wisdom into contemporary practices.